2019
DOI: 10.1007/s10802-019-00577-8
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Antenatal Risk and Kindergarten Readiness in Preterm-Born Preschoolers

Abstract: A suboptimal intrauterine environment is thought to increase the probability of deviation from the typical neurodevelopmental trajectory, potentially contributing to the etiology of learning disorders. Yet the cumulative influence of individual antenatal risk factors on emergent learning skills has not been sufficiently examined. We sought to determine whether antenatal complications, in aggregate, are a source of variability in preschoolers' kindergarten readiness, and whether specific classes of antenatal ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
(64 reference statements)
1
6
0
1
Order By: Relevance
“…This finding suggests that teachers may play a vital role in promoting emotional socialization, even when children have characteristics (i.e., CU traits) that might otherwise negatively impact their relationships with others. In contrast, qualitative studies suggest that teachers perceive fewer reward-based strategies as effective for children high in CU traits (Allen et al, 2016(Allen et al, , 2018, and longitudinal research in the current sample found that CU traits were related to teachers reducing their use of rewards over time (Hwang et al, 2020). Teachers' less frequent use of rewards and greater use of harsh discipline may elicit poor quality of teacherchild affiliation (De Jong et al, 2014), and have shown significant associations with CU traits (Allen et al, 2018).…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…This finding suggests that teachers may play a vital role in promoting emotional socialization, even when children have characteristics (i.e., CU traits) that might otherwise negatively impact their relationships with others. In contrast, qualitative studies suggest that teachers perceive fewer reward-based strategies as effective for children high in CU traits (Allen et al, 2016(Allen et al, , 2018, and longitudinal research in the current sample found that CU traits were related to teachers reducing their use of rewards over time (Hwang et al, 2020). Teachers' less frequent use of rewards and greater use of harsh discipline may elicit poor quality of teacherchild affiliation (De Jong et al, 2014), and have shown significant associations with CU traits (Allen et al, 2018).…”
mentioning
confidence: 55%
“…Children rated items on a 3-point scale ranging from 0 (not true) to 2 (certainly true). The reliability and construct validity of the revised antisocial behavior scale was established in a prior study using the same sample, showing significant correlations with both CU traits and teacher harsh discipline (Hwang et al, 2020; T1, α = .88; T2, α = .90; T3, α = .92).…”
Section: Antisocial Behaviormentioning
confidence: 90%
See 2 more Smart Citations
“…Therefore, frequent changes in foster care placement can be a risk factor for healthy development (Lewis, Dozier, Ackerman, & Sepulveda-Kozakowski, 2007 ; Newton, Litrownik, & Landsverk, 2000 ; Rubin, O’Reilly, Luan, & Localio, 2007 ). Furthermore, the duration of foster care stay was also associated with physical and mental well-being in prior studies (Fallesen, 2013 ; Frenkel et al, 2020 ; Navarro-Soria, Servera, & Burns, 2020 ).…”
Section: Introductionmentioning
confidence: 67%